Prevalencia del desgaste dental en estudiantes de la Facultad de Odontología de la Universidad de Las Américas - Endara Gómez, Leslie Johanna (2018)
Dental abrasion is a non-carious chronic loss in response to several multifactorial processes of the mineralized structures of the teeth that can be attrition, erosion, abrasion and abfraction. The study aims to determine the prevalence, grade and type of tooth wear in students of the Faculty of Dentistry of the University of the Americas. Methods and materials. A descriptive study was conducted, where the sample was constituted by 106 students. In order to realize this study, it was carried out a dental clinical examination to evaluate the following factors: tooth wear, grade and type of tooth wear (abrasion, attrition, erosion, abfraction). Results: The results showed that there is a prevalence of dental wear of the 95.3% corresponding to 101 students. In terms of age, the group with more relevance was the 21 to 25 years who presented a 68.8%. It was also found a greater prevalence of tooth wear in the females with a 67.9%, the grade of dental wear more frequent is the degree 1 with 78.3%. Finally, attrition was the type of tooth wear more frequent with a 73.6%, of the students examined.